THE EFFECT OF ALKALOIDS ON THE HUMAN BODY - Abdukarimova Farida Abdumalik qizi (Research Focus International Scientific Journal, 2024)
"Alkaloids" are basic nitrogen-containing organic compounds found in plants and animals. By the 19th century, strychnine, quinine, caffeine, atropine, ephedrine and others were isolated from alkaloids. Academicians S.Yu.Yunusov and O.S. Sadikov’s work with his students on alkaloids. According to the studies by S.Yu.Yunusov, alkaloids are most abundantly collected from the shoot of the plant in early spring, from the seeds of annual plants in autumn, from the roots and seeds of perennial plants. Chemistry of Plant Substances of the Academy of Sciences of Uzbekistan in 1943-1993. 266 plant species belongs to 29 families, 345 species were studied at the institute under the leadership of S. Yu. Yunusov, and 913 alkaloids were isolated from them.